Presence of multiple corpora lutea affects the luteolytic response to prostaglandin F2α in lactating dairy cows - Fernando LÓPEZ-GATIUS (The Society for Reproduction and Development, 2021)
Since the 1970s, luteolytic doses used for synchronizing estrus in dairy cattle have remained unchanged. This study aimed to evaluate the dose-response effect of prostaglandin F2α (PGF2α), which is used for synchronizing estrus, and subsequent fertility in cows with two or more corpora lutea (CL). The study population consisted of 1,683 cows with a single CL (1CL), 501 cows with multiple CL receiving a single dose of PGF2α (2CL1), and 252 cows with multiple CL receiving a 1.5 × PGF2α dose (2CL1.5). Cows with a single CL (n = 1,245) showed estrus significantly (P < 0.01) earlier (3.01 ± 1.23 days; mean ± SD) than cows with multiple CL (n = 287; 3.33 ± 1.69 days). Using 1CL cows as reference, the odds ratio (OR) for the estrus response in 2CL1 cows was 0.13 (P < 0.0001), whereas the ORs for estrus response and pregnancy of 2CL1.5 cows were 1.8 (P = 0.0001) and 1.7 (P = 0.001), respectively. Based on the results for only the 2CL1 cows, the OR for the estrus response was 0.7 (P = 0.01) for cows producing ≥ 45 kg of milk at treatment, compared to the remaining cows producing < 45 kg of milk. Our results showed that the presence of multiple CL reduced the estrus response to that induced by a single PGF2α dose and milk production was inversely associated with this response, whereas an increased PGF2α dose improved the estrus response. Therefore, an increase in the standard PGF2α dose is recommended.